MENGAMPUNI (ἀπολυω) SIKAP ETIS YESUS TERHADAP PERCERAIAN: Kajian Hermeneutik Matius 19:1-9 - Elsye Mastika Balebu (Sekolah Tinggi Teologi Injili Arastamar (SETIA) Jakarta, 2022)
This article proposes a theological construction of Jesus’ ethical attitude towards divorce. The conflict between the socio-political practice that legalizes divorce and the narrative of religious rhetoric against divorce is the cause of many divorces in Christian families. An understanding of the ethical morality of Christians towards divorce shows that there is an excessive adherence to the biblical text without considering the context. I use hermeneutic principles through the dialectic of the text and the context of the Gospel of Matthew 19:1-9 as the method used by Jesus to understand the reality of the Torah text. This effort aims to assist Pastors in pastoral care when accompanying families who are about to divorce. This article uses a literature research method with a text centred (synchronic) approach and a qualitative method to examine the results of field research. The results showed that the text of Matthew 19:1-9 was about to criticize the attitude of Pharisees who wanted to trap Jesus through the question of divorce. It turns out that Jesus has His own Halakhah, that is, forgiveness to avoid divorce.